PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR SISWA DALAM MENGULAS KARYA FIKSI KELAS VIII SMP NEGERI 1 PAGUYAMAN - Mato, Meylan; Muslimin; Eka Sartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the effect of the talking stick leaming model on the learning outcomes of Grade VIII students in reviewing fictional works at SMP Negeri 1 Paguyaman. The research employs a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design.The population consists of all 111 eighth-grade students. The sample, celected through purposive sampling, includes 54 students: 27 students from Grade VIII.2 as the experimental group using the talking stick model and 27 students from Grade VIII. 4 as the control group using a conventional learning model. Data were collected through tests and analyzed using a t-test, with the data first undergoing normality and homogeneity testing. The findings indicate that the talking stick leaming model effectively enhanced student participation and motivation and improved learning outcomes in Grade VIil at SMP Negeri 1 Paguyaman. This is demonstrated by the results, where the experimental group (Grade VIII.2) had an average pretest score of 43.89, which increased to 83.70 in the posttgem.comnparison, the control group (Grade VIII.4) had lan average pretestscon The t-test results showed a significance a and a posttest score of 74.63. SP2-Tailed) of 0.000, which is less than 0.05, indicating that HO is rejected accepted. This confirms a significant difference between the experimen and control&sups.